SOME USES OF ARISTOCLES AND NUMENIUS IN EUSEBIUS' PRAEPARATIO EVANGELICA - Carriker, Andrew J. (The journal of theological studies, 1996)
ANDREW J. CARRIKER; SOME USES OF ARISTOCLES AND NUMENIUS IN EUSEBIUS' PRAEPARATIO EVANGELICA, The Journal of Theological Studies, Volume 47, Issue 2, 1 October